Editorial (Intervention. European Journal of Economics and Economic Policies, 2012)
The euro crisis remains at the centre of the economic policy debate. The member states of the European Monetary Union have adopted fiscal austerity programmes which imply a very restrictive overall fiscal stance for the years to come. Stefan Ederer argues in the Forum section of this issue that the current reforms are largely missing the point and neglect the structural causes of the crisis. Ederer pleads for a better coordination of fiscal policies, based on public expenditure paths rather than uniform deficit targets. A more balanced approach for fiscal policies and vigorous stabilisation measures on the financial markets are prerequisites for the return to longer term economic stability and the reduction of unemployment. The Forum section is completed by an interview with Malcolm Sawyer.
Keywords: 330